Socialization of Rules of The Games and Management of Volleyball Match Events for Physical Education Students of Lambung Mangkurat University - Norma Anggara; Elsa Ariestika; Rizal Ardiansyah; Perdinanto; Mita Erliana (Journal Social Science And Technology For Community Service, 2026)
Rules of the games and management of volleyball match events are important roles to equip students of the Physical Education study program, Lambung Mangkurat University, where the output after graduating from college is not only to become teachers, but there are other field abilities such as managing sports match events. Despite the low experience and ability of students in managing match event management, a socialization of the rules of the games and management of volleyball match events for physical education students at Lambung Mangkurat University was carried out to improve event management skills among students in volleyball sports in Banjarbaru City, South Kalimantan. The method used in this activity consists of (1) planning stage, (2) implementation stage, (3) implementation stage, (4) evaluation stage with an observational study approach with qualitative methods. The results of this community service implementation show that the Socialization of Rules of the Games and Management of Volleyball Match Events for Physical Education Students at Lambung Mangkurat University has succeeded in providing an initial foundation in increasing interest and knowledge about volleyball refereeing to volleyball match management. Although it is acknowledged that the results of the observational analysis have not shown a maximum impact on the overall understanding of the participants, they have had a real positive impact. This activity provided insight through theoretical and practical approaches into volleyball regulations and refereeing.